Asymmetric coordination induced oxygen-rich vacancy of iron-doped nickel phosphate electrocatalytic material and preparation method and application thereof
Patent Information
- Application Number
- CN202610820117.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-09-18
AI Technical Summary
[0006]本发明旨在克服现有技术的不足,解决现有的磷酸镍基催化剂存在的电荷转移效率较低、内部大量活性组分无法充分参与反应等问题,提供一种不对称配位诱导富氧空位的铁掺杂磷酸镍电催化材料及其制备方法与应用
本发明采用电沉积的方法,在泡沫镍上构建了一种具有不对称Fe-O(P)-Ni配位和丰富氧空位的催化剂,其所具有的不对称配位和丰富的氧空位进行耦合,有效提升了电催化材料的电催化OER活性,使得其在碱性环境中展现出优异的电催化性能,具体地包括较低的塔菲尔斜率、电荷转移阻抗、更大的电化学活性面积与双电层电容Cdl,且在恒电位电解条件下可稳定运行不少于24小时。本发明所制备的电催化材料可直接应用于两电极体系电解水装置,为高效非贵金属电催化剂的设计与制备提供了新思路,对推动绿色能源转化领域的发展具有重要意义。
Smart Images

Figure CN122773398A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of new energy, specifically to an iron-doped nickel phosphate electrocatalytic material with asymmetric coordination-induced oxygen-rich vacancies, its preparation method, and its application. Background Technology
[0002] Hydrogen energy, with its high energy density and zero carbon emissions, is considered an ideal clean energy source for addressing the energy crisis and environmental issues. Among various hydrogen production technologies, electrochemical water splitting has become an important research direction in the field of sustainable energy due to its advantages such as high efficiency, stability, and environmental friendliness.
[0003] The water electrolysis process comprises two half-reactions: the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER). The OER involves a multi-step four-electron-proton coupling transfer process, exhibiting slow intrinsic reaction kinetics, which is a key bottleneck limiting the energy conversion efficiency of water electrolysis. Currently, the most widely used commercial OER electrocatalysts are still noble metal-based materials (such as RuO2 and IrO2), but their high cost and scarce reserves make it difficult to meet the needs of large-scale industrial applications. Therefore, developing non-noble metal OER electrocatalysts based on abundant crustal elements, possessing both high catalytic activity and high stability, has significant research value and application prospects.
[0004] Among numerous non-noble metal catalysts, transition metal phosphates have attracted widespread attention due to their unique structural openness and good chemical stability. Nickel phosphate (NPO), with its tetrahedral porous framework structure, provides favorable conditions for the exposure of catalytic active sites and reaction mass transfer. Studies have shown that under alkaline OER conditions, phosphate-based materials typically undergo in-situ surface reconstruction, transforming into (oxy)hydroxide active species. Therefore, precisely controlling the reconstruction process through pre-catalyst structural design is an effective strategy for improving OER catalytic performance.
[0005] However, existing nickel phosphate-based catalysts still have significant shortcomings in terms of electronic structure and reconstruction regulation: on the one hand, the inherent electronic structure leads to low charge transfer efficiency and unsatisfactory adsorption / desorption capacity for reaction intermediates; on the other hand, material reconstruction is usually limited to the near-surface region, easily forming a core-shell structure, where a large number of internal active components cannot fully participate in the catalytic reaction, resulting in low atom utilization. These problems lead to excessively high OER overpotential and increased Tafel slope in the catalysts. How to regulate the coordination environment of nickel phosphate materials at the atomic level, overcome the limitations of their inherent electronic structure, and achieve deep and uniform interface reconstruction remains a key technical problem that urgently needs to be solved in this field. Summary of the Invention
[0006] This invention aims to overcome the shortcomings of existing technologies and solve problems such as low charge transfer efficiency and insufficient participation of a large number of active components in the reaction of existing nickel phosphate-based catalysts. It provides an iron-doped nickel phosphate electrocatalytic material with asymmetric coordination-induced oxygen-rich vacancies, its preparation method, and its applications. The electrocatalytic material provided by this invention has asymmetric Fe-O-Ni heterometallic oxygen bridges and oxygen vacancies. This asymmetric structure and oxygen vacancies are beneficial to improving the charge transfer efficiency of the material and optimizing the RDS (rate-determining step) in the OER pathway, thereby enhancing the electrocatalytic activity of the material.
[0007] To achieve the above objectives, a first aspect of the present invention provides an iron-doped nickel phosphate electrocatalytic material with asymmetric coordination-induced oxygen-rich vacancies, wherein the material comprises a nickel phosphate substrate and Fe element doped in the nickel phosphate substrate, wherein the Fe element is in the form of Fe... 2+ and Fe 3+ It exists and forms an asymmetric Fe-O-Ni heterometallic oxygen bridge bond with Ni in the material through oxygen, and optionally forms an asymmetric Fe-OP-Ni heterometallic oxygen bridge bond with Ni in the material through oxygen and phosphorus, and the material also has oxygen vacancies.
[0008] The catalyst prepared by this invention has a large number of oxygen vacancies. Its asymmetric Fe-O(P)-Ni coordination energy couples with the oxygen vacancies, inducing deep reconstruction of the material in the OER process. The reconstructed material effectively modulates the d-band center of the Ni site, causing it to move towards the Fermi level. This not only enhances the water adsorption capacity but also optimizes the RDS in the OER pathway, thus giving the material excellent electrocatalytic OER activity.
[0009] A second aspect of this invention provides a method for preparing an iron-doped nickel phosphate electrocatalytic material with asymmetric coordination-induced oxygen-rich vacancies, wherein the preparation method includes: Using a mixture containing nickel, iron, and phosphate sources as the electrolyte, electrodeposition was performed in a three-electrode system using cyclic voltammetry with a potential window of -0.95V to 1.2V (vs. RHE), thereby depositing iron-doped nickel phosphate electrocatalytic materials on the working electrode.
[0010] The third aspect of this invention provides the application of the iron-doped nickel phosphate electrocatalyst material described in the first aspect of this invention or the iron-doped nickel phosphate electrocatalyst material prepared by the preparation method described in the second aspect of this invention in the electrolysis of water to produce hydrogen. Attached Figure Description
[0011] Figure 1 SEM images of the material prepared in Example 1 and the corresponding nanoflower particle size distribution diagram; Figure 2 TEM image of the material prepared in Example 1; Figure 3 The XRD pattern of the material obtained in Example 1; Figure 4 XPS image of the material prepared in Example 1; Figure 5 The image shows a TEM image of the material prepared in Example 1 after undergoing an OER reaction. Figure 6 Bode plot and Raman plot of the material obtained in Example 1; Figure 7 Linear sweep slicing (LSV) curves of the material prepared in Example 1; Figure 8 The Tafel slope diagram of the material prepared in Example 1; Figure 9 The impedance (EIS) diagram of the material prepared in Example 1; Figure 10 The cyclic voltammetry (CV) curves and Cdl plots of the material obtained in Example 1 are shown. Figure 11 The stability test diagram is shown for the material prepared in Example 1. Figure 12 The figures show the two-electrode performance and stability test results of the MEA water electrolysis device (HER-OER) assembled with the electrocatalyst prepared in Example 1 and the Pt / C catalyst. Detailed Implementation
[0012] The specific embodiments of this application will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit this application.
[0013] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0014] Furthermore, the term "and / or" in the specification and claims is used to describe the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. The character " / " generally indicates that the preceding and following related objects have an "or" relationship.
[0015] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0016] The first aspect of the present invention provides an iron-doped nickel phosphate electrocatalytic material with asymmetric coordination-induced oxygen-rich vacancies, wherein the material comprises a nickel phosphate substrate and Fe element doped in the nickel phosphate substrate, the Fe element existing as Fe2+ and Fe3+, and forming an asymmetric Fe-O-Ni heterometallic oxygen bridge bond with Ni in the material through oxygen, and optionally forming an asymmetric Fe-OP-Ni heterometallic oxygen bridge bond with Ni in the material through oxygen and phosphorus, and the material also has oxygen vacancies.
[0017] The catalyst prepared by this invention has a large number of oxygen vacancies. Its asymmetric Fe-O(P)-Ni coordination energy couples with the oxygen vacancies, inducing deep reconstruction of the material in the OER process. The reconstructed material effectively modulates the d-band center of the Ni site, causing it to move towards the Fermi level. This not only enhances the water adsorption capacity but also optimizes the RDS in the OER pathway, thus giving the material excellent electrocatalytic OER activity.
[0018] Preferably, based on the total amount of the material, the amount of Fe in the material is 2-3 at.%. In this application, the Fe doping is not simply mixed in the material, but rather forms a strong chemical bond with Ni and P through oxygen bridges, constructing an asymmetric coordination unit. The amount of Fe affects the distribution of the electron cloud in the asymmetric heterometallic oxygen bridge bond, thereby affecting the electrocatalytic OER activity of the material. Based on the total amount of the material, the amount of Fe in the material can be 2 at.%, 2.2 at.%, 2.4 at.%, 2.6 at.%, 2.8 at.%, 3 at.%, and any value between any two of these values.
[0019] Preferably, based on the total amount of oxygen in the material, the amount of oxygen vacancies in the material is 50-60 at.%. The doped Fe forms an asymmetric Fe-O(P)-Ni structure (including Fe-O-Ni bonds and Fe-OP-Ni bonds). This asymmetric structure makes some oxygens in the lattice (especially bridging oxygens) unstable and easier to be "pulled away" to form vacancies. The formed oxygen vacancies are coupled with the asymmetric structure, further enhancing the OER activity of the material. Based on the total amount of oxygen in the material, the amount of oxygen vacancies in the material can be 50 at.%, 52 at.%, 55 at.%, 58 at.%, 60 at.%, and any value between any two of them.
[0020] Preferably, the material is in the form of nanosheets, and multiple nanosheets of the material self-assemble to form nanoflowers. The nanoflowers formed by the self-assembly of the material give it a three-dimensional porous structure, which is beneficial for exposing more active sites, thereby enabling the material to participate more fully in the catalytic reaction, improving atom utilization, and thus enhancing the catalytic activity of the material.
[0021] Preferably, the thickness of the nanosheet-like material is 0.9-1.2 nm. The sheet-like shape of the material facilitates the exposure of more active sites, thereby improving atom utilization.
[0022] Preferably, the diameter of the self-assembled nanoflower is 120-170 nm. The diameter of the nanoflower can be 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, or any value between any two of these numbers.
[0023] Preferably, the material further includes a substrate on which the nickel phosphate substrate is deposited.
[0024] Preferably, the substrate is selected from any one of nickel mesh, nickel foam, copper foam, carbon paper, and carbon cloth.
[0025] A second aspect of this invention provides a method for preparing an iron-doped nickel phosphate electrocatalytic material with asymmetric coordination-induced oxygen-rich vacancies, wherein the preparation method includes: Using a mixture containing nickel, iron, and phosphate sources as the electrolyte, electrodeposition was performed in a three-electrode system using cyclic voltammetry with a potential window of -0.95V to 1.2V (vs. RHE), thereby depositing iron-doped nickel phosphate electrocatalytic materials on the working electrode.
[0026] This application does not impose special requirements on the electrodes in the three-electrode system; any commonly used electrodes in the field are acceptable, as long as they can be deposited within the same voltage range after conversion according to the Nernst equation. For example, the working electrode can be a nickel mesh, nickel foam, copper foam, carbon paper, carbon cloth, etc., and the reference electrode can be Pt. When selecting a phosphate source, it is important to ensure that its cation does not contain the metal of the working electrode. For example, if the working electrode is nickel, the cation matching the phosphate group must not be nickel, i.e., nickel phosphate should not be used. There are no special requirements for the nickel source, iron source, and phosphate source, as long as they are dissolved in the solvent used in the electrolyte, which is generally water.
[0027] Preferably, the number of electrodeposition cycles is 1-10.
[0028] Preferably, the number of electrodeposition cycles is 4-6. The number of cycles can be 1, 2, 4, 6, 8, 10, or any value between any two of these numbers.
[0029] Preferably, the molar ratio of nickel in the nickel source, iron in the iron source, and phosphate in the phosphate source in the electrolyte is 3:0.5-1.5:1. The molar ratio of each component in the electrolyte affects the asymmetric structure and the distribution of oxygen vacancies, thereby affecting the catalytic activity of the material. The molar ratio of nickel, iron, and phosphate in the electrolyte can be 3:0.5:1, 3:0.6:1, 3:0.7:1, 3:0.8:1, 3:0.9:1, 3:1:1, 3:1.2:1, 3:1.5:1, or any value between any two of these ratios.
[0030] Preferably, the concentration of nickel in the nickel source of the electrolyte is 0.03 mol / L, the concentration of iron in the iron source is 0.005-0.015 mol / L, and the concentration of phosphate in the phosphate source is 0.01 mol / L. The concentration of iron in the electrolyte can be 0.005 mol / L, 0.07 mol / L, 0.08 mol / L, 0.01 mol, 0.012 mol, 0.013 mol, 0.014 mol, 0.015 mol, or any value between any two of these values.
[0031] Preferably, the nickel source is selected from at least one of nickel sulfate, nickel chloride, nickel nitrate, nickel acetate, and nickel aminosulfonate and their corresponding hydrates.
[0032] Preferably, the iron source is selected from at least one of ferrous nitrate, ferrous sulfate, ferrous ammonium sulfate, and ferrous chloride and their corresponding hydrates.
[0033] Preferably, the phosphate source is selected from sodium hypophosphite and / or potassium hypophosphite.
[0034] Preferably, in the three-electrode system, the working electrode is a nickel electrode, the counter electrode is a Pt electrode, and the reference electrode is selected from at least one of a saturated calomel electrode, an Ag / AgCl electrode, and a mercuric oxide electrode.
[0035] In addition, the method also includes pretreatment of the working electrode, which involves ultrasonically cleaning the working electrode in hydrochloric acid, ethanol and deionized water respectively, and drying it after cleaning to obtain the pretreated working electrode.
[0036] The third aspect of this invention provides the application of the iron-doped nickel phosphate electrocatalyst material described in the first aspect of this invention or the iron-doped nickel phosphate electrocatalyst material prepared by the preparation method described in the second aspect of this invention in the electrolysis of water to produce hydrogen.
[0037] Compared with the prior art, the present invention has the following significant advantages: This invention employs electrodeposition to construct a catalyst with asymmetric Fe-O(P)-Ni coordination and abundant oxygen vacancies on nickel foam. The coupling of this asymmetric coordination and abundant oxygen vacancies effectively enhances the electrocatalytic OER activity of the electrocatalytic material, resulting in superior electrocatalytic performance in alkaline environments. Specifically, this includes a lower Tafel slope, charge transfer impedance, a larger electrochemical active area, and a higher double-layer capacitance (Cdl). Furthermore, it can operate stably for at least 24 hours under constant-potential electrolysis conditions. The electrocatalytic material prepared by this invention can be directly applied to a two-electrode water electrolysis device, providing a new approach for the design and preparation of highly efficient non-precious metal electrocatalysts and holding significant importance for promoting the development of green energy conversion.
[0038] The preparation and performance testing process involved in this invention is simple and easy to implement, with low reagent consumption and obvious cost advantages. The preparation process is simple and easy to implement, the raw materials are widely available and inexpensive, the reaction conditions are mild, and it has good prospects for industrial application.
[0039] The present invention will be further described in detail below with reference to specific embodiments, but the implementation of the present invention is not limited thereto. Unless otherwise specified, the test methods and testing equipment used in the following embodiments are conventional test methods and testing equipment in the art.
[0040] Example 1 Nickel foam with a size of 1cm×1cm was cut, placed in 1mol / L HCl solution and sonicated for 10min, then ultrasonically cleaned with anhydrous ethanol and deionized water for 8min each, and dried at 60℃ to obtain the pretreated working electrode, denoted as NF electrode; Dissolve 0.174 g Ni (NO3)2・6H2O, 0.082 g Fe (NO3)3・9H2O and 0.021 g NaH2PO2・H2O in 20 mL of deionized water and sonicate for 10 min until homogeneous to obtain the electrolyte. Electrodeposition was performed using a three-electrode system: an NF electrode as the working electrode, a Hg / Hg2Cl2 electrode as the reference electrode, and a Pt electrode as the counter electrode, with a spacing of 1 cm between the electrodes. Cyclic voltammetry was used for deposition, with a potential window of -0.95 V to 1.2 V (vs. RHE) and 5 cycles. After deposition, the working electrode was removed, washed sequentially with ethanol and deionized water, and dried in an oven at 60 °C. Iron-doped nickel phosphate electrocatalyst material was thus obtained on the working electrode. Subsequent experiments were conducted using this iron-doped nickel phosphate electrocatalyst material deposited on the working electrode, and the electrode with the electrocatalyst deposited was designated as the Fe-NPO electrode.
[0041] Comparative Example 1 The procedure was carried out in accordance with Example 1, except that the electrolyte did not contain Fe(NO3)3・9H2O, and the electrode was designated as NPO.
[0042] Comparative Example 2 The procedure was carried out in accordance with Example 1, except that the electrolyte did not contain Ni(NO3)2・6H2O, and the electrode was designated as FPO.
[0043] Test Example 1: Characterization of Electrocatalytic Materials (1) The electrocatalyst prepared in Example 1 was scanned using a scanning electron microscope, and the results are as follows: Figure 1 As shown, where Figure 1 (a) is the SEM image of the material. Figure 1 (b) is the particle size distribution histogram of the material. As can be seen from the figure, the material exhibits a three-dimensional open hierarchical morphology composed of self-assembled nanosheet structural units, forming a uniform nanoflower-like structure. This unique structure constructs a multi-level porous network, which is expected to effectively suppress the aggregation of nanounits and increase the electrochemical surface area. The thickness of individual nanosheet materials ranges from 0.9 to 1.2 nm, and the diameter of the nanoflowers ranges from 120 to 170 nm. To quantify the size of its structural units, we performed statistical analysis on more than 100 particles, obtaining the corresponding particle size distribution histogram (…). Figure 1 (b) Statistical results show that the Fe-NPO catalyst exhibits a good normal particle size distribution with an average diameter of approximately 145 nm, confirming the good monodispersity and uniformity of the material synthesis process. This open hierarchical nanoflower-like morphology is beneficial for exposing more active sites and promoting electrolyte penetration, and will demonstrate structural advantages in subsequent electrochemical tests.
[0044] (2) The catalyst in Example 1 was scanned by transmission electron microscopy (TEM), and the results are as follows: Figure 2 As shown, where Figure 2 (a) is a transmission electron microscope (TEM) image of Fe-NPO. Figure 2 (b) is a high-resolution transmission electron microscope (HRTEM) image of Fe-NPO. Figure 2 (c) Fe-NPO along the Ni2(P2O7)(031) crystal plane ( Figure 2 (b) The inverse Fourier transform (IFFT) plot obtained from region c) Figure 2 (d) represents Fe-NPO along the Ni2(P2O7)(311) crystal plane. Figure 2 (b) The inverse Fourier transform (IFFT) plot obtained by transforming region d) Figure 2 (e) is the elemental mapping (EDS) diagram of Fe-NPO. The inverse Fourier transform diagram shows that the main component of the surface material is Ni2(P2O7). Elemental mapping analysis shows that Fe, Ni, P, and O elements are uniformly distributed on the catalyst.
[0045] (3) The catalysts in Example 1 and Comparative Examples 1 and 2 were irradiated with X-ray diffractometer, and the results are as follows: Figure 3 As shown in (a), the X-ray powder diffraction (XRD) pattern shows that the diffraction peaks at 44.5°, 51.8° and 76.4° correspond to the (111), (200) and (220) crystal planes of nickel (PDF#004-0850), respectively. No obvious diffraction peaks were detected for Fe-NPO, NPO and FPO, indicating that the electrocatalyst is amorphous.
[0046] according to Figure 3 (b) The EDS analysis revealed that the atomic fraction of Fe in Example 1 was 2.27 at.%.
[0047] (4) The catalysts in Example 1 and Comparative Examples 1 and 2 were irradiated by X-ray photoelectron spectroscopy, and the results are as follows: Figure 4 As shown, where Figure 4 (a) is the Fe 2p diagram. Figure 4 (b) is the Ni 2p plot. Figure 4 (c) is the O 1s plot, and (d) is the P 2p plot.
[0048] As can be seen from the figure, Ni, Fe, P and O are present in Fe-NPO. The Fe2p spectrum of Fe-NPO is deconvolved into four main spin-orbit pairs. Figure 4(a) is attributed to Fe2+ (723.81 eV / 710.91 eV) and Fe3+ (726.65 eV / 713.84 eV), accompanied by two satellite (saturated) signals at 731.47 and 718.21 eV, in the Ni2p XPS spectrum of Fe-NPO ( Figure 4 (b) The eight deconvolution peaks correspond to the spin orbitals of Ni2 p3 / 2 (Ni0 at 852.83 eV; Ni2+ at 855.62 eV, Ni2+ at 855.62 eV, Ni2+ at 855.62 eV, Ni2+ at 855.62 eV); Ni3+ at 856.42 eV), Ni2 p1 / 2 (Ni0 at 870.14 eV, Ni2+ at 873.03 eV; Ni3+ at 874.44 eV) and two satellite peaks (861.56 and 879.62 eV). Notably, the Ni2 p3 / 2 peak in Fe-NPO is positively shifted by approximately 0.13 eV relative to the peak in NPO. Furthermore, the Ni3+ / Ni2+ ratio of Fe-NPO (0.70) is significantly higher than that of NPO. The P2p spectrum of Fe-NPO shows a main peak at approximately 132.77 eV. Figure 4 (d) is classified as an oxidized phosphorus substance (PO3-4).
[0049] The P2p peak of Fe-NPO was negatively shifted by 0.10 eV and 0.13 eV compared to the P2p peaks of NPO and FPO, respectively. Figure 4 (d) The four peaks at 530.30, 531.16, 532.09, and 533.36 eV can be attributed to lattice oxygen, oxygen vacancies (Ov), and OH / PO groups ( Figure 4 (c) Compared to NPO and FPO, the oxygen vacancy peak intensity of Fe-NPO is significantly increased and negatively shifted. This is likely due to the formation of the Fe-O(P)-Ni para site, where the charge redistribution on the oxygen Fe-O(P)-Ni bond causes some electrons to be withdrawn from Ni and aggregate on the relatively more electrophilic O(P). This electronic interaction leads to the observed binding energy shift. Calculations using the oxygen vacancy peak area and the total oxygen peak area show that the oxygen vacancy rate of Fe-NPO is 55.2 at.%.
[0050] By introducing Fe into nickel phosphate and utilizing the strong electron-withdrawing ability of Fe³⁺, the electron cloud arrangement around Ni atoms was altered (electronic effect), causing Ni to lose electrons and O(P) to gain electrons. This indicates that electrons were redistributed throughout the "Fe-O(P)-Ni" chain, proving that Fe is not simply mixed in the material, but rather forms a strong chemical bond with Ni and P through oxygen bridges, constructing an asymmetric coordination unit. This, in turn, shifts the d-band center of Ni to a more ideal position (optimization), making the catalyst surface better at capturing water molecules and catalyzing the formation of oxygen.
[0051] In addition, quantitative analysis of oxygen vacancy concentration ( Figure 4 (c) shows that Fe-NPO (with up to 55.2 at.%) has a significantly higher oxygen vacancy rate compared to NPO (38.6 at.%) and FPO (42.7 at.%). These results indicate a high oxygen vacancy concentration in Fe-NPO.
[0052] (5) The catalyst after CP testing was scanned by transmission electron microscopy (TEM), and the results are as follows: Figure 5 As shown in (a), the HRTEM image of Fe-NPO after OER shows clear lattice stripes with interplanar spacings of 0.269 nm and 0.158 nm, corresponding to the (130) and (220) planes of Ni(Fe)OOH. Figure 5 In the selected area electron diffraction (SAED) pattern shown in (b), diffraction rings belonging to the Ni(Fe)OOH phase can be observed. The above lattice fringes and diffraction pattern together indicate that Fe-NPO undergoes surface reconstruction during the OER process, transforming into active species composed of the Ni(Fe)OOH phase.
[0053] (6) To investigate the reaction mechanism in the OER process, the Bode plots obtained from EIS testing of Example 1 and Comparative Example 1 were analyzed, as follows: Figure 6As shown in (a)-(b), the Bode plots of potential changes further reveal the OER mechanism of Fe-NPO and NPO within the frequency range of 100 kHz-0.01 Hz. The low-frequency region (10⁻²-10¹ Hz) in the Bode plot is related to the adsorption behavior of surface intermediates, while the high-frequency region (10¹-10⁵ Hz) is related to electro-oxidation within the electrode. For Fe-NPO, electro-oxidation occurs in the high-frequency region, while OER occurs in the low-frequency region. When the potential rises to 1.40 V (vs. RHE), the high-frequency peak of Fe-NPO drops sharply, indicating the formation of high-valence nickel species; subsequently, a new peak appears in the low-frequency region, corresponding to the diffusion of active species to the electrode surface and their participation in the redox process. In the range of 1.42-1.60 V, the low-frequency peak shifts to the high-frequency region and the phase angle decreases, corresponding to the formation of active hydroxides. In contrast, NPO exhibits a higher electro-oxidation potential and an OER onset potential of 1.46 V (compared to only 1.35 V for Fe-NPO). These results indicate that the Fe-NPO reaction kinetics are faster, attributed to its rapid surface reconstruction.
[0054] Furthermore, the Raman spectra of the catalyst after CA testing (conducted in a three-electrode system, with Fe-NPO material prepared in Example 1 / NPO material prepared in Comparative Example 1 as the working electrode, saturated calomel as the reference electrode, a platinum sheet (1×1 cm²) as the counter electrode, and a 1.0 M KOH aqueous solution as the electrolyte) were tracked using in-situ Raman spectroscopy. An electrochemical workstation (CHI 760E) was used to apply a series of constant voltages (relative to the reversible hydrogen electrode, RHE), specifically 1.12 V, 1.22 V, 1.32 V, 1.42 V, 1.52 V, 1.62 V, and 1.72 V. At each voltage, the potential was kept constant for 10 minutes to allow the electrode surface to reach a stable electrochemical state. The treated electrodes were dried at room temperature and then sealed for Raman spectroscopy testing. The dynamic reconstruction process of Fe-NPO and NPO under different voltages was investigated. Figure 6 (c) and (d) at 1.12 V, no Raman signal was detected in the range of 200-900 cm-1; when the potential was raised to 1.22 V and above, characteristic peaks of NiOOH appeared at 474.8 and 556.7 cm-1, and the intensity increased with increasing voltage. At the same time, characteristic peaks of FeOOH appeared at 676.1 cm-1, indicating that Fe-NPO underwent electrochemical surface reconstruction during the OER process. The phase reconstruction potential of Fe-NPO was 1.22 V, which was significantly lower than that of NPO (1.52 V). Figure 6 The 3D contour plots in (e) and 6(f) further show a significant enhancement in the (oxy)hydride spectral signal of Fe-NPO.
[0055] The above results indicate that the OER activity of Fe-NPO originates from the (oxy)hydroxide generated in situ on the catalyst surface. The optimized Fe-NPO can undergo surface reconstruction at a lower potential, which is the fundamental reason for its high activity.
[0056] Test Example 2: Electrochemical Performance Test All electrochemical tests were performed at room temperature (RT, 25°C) using a standard three-electrode system with 1 mol / L KOH as the electrolyte, a platinum sheet as the counter electrode, a saturated calomel electrode (SCE, Hg / Hg2Cl2 / KCl) as the reference electrode, and the electrode prepared in Example 1 or Comparative Example 1 / 2.
[0057] To compare the OER activity, a commercial RuO2 catalyst was uniformly loaded onto nickel foam with a loading of approximately 0.5 mg·cm⁻² as a working electrode for comparison. (The preparation method was as follows: 5 mg of commercial RuO2 (20 wt%) was dispersed in a solution of 480 μL DI water, 6480 μL anhydrous ethanol, and 40 μL Nafion solution (5 wt%), then sonicated to form a uniform ink. 100 μL of the ink was then uniformly dropped onto pretreated NF (1 × 1 cm⁻²), and dried overnight at room temperature. The mass loading of RuO2 in the NF was 0.5 mg cm⁻², measured by weighing before and after coating.)
[0058] (1) Linear sweep voltammetry (LSV) was used for testing at a scan rate of 5 mV·s⁻¹. All LSV data were corrected for 95% ohmic potential drop (iR). Potentials were converted to the reversible hydrogen electrode (RHE) scale, and the correction formula was: E=E+0.0592×pH+0.241-iR×95%, where i is the current density and R is the uncompensated solution resistance obtained from electrochemical impedance spectroscopy (EIS).
[0059] (2) The Tafel slope is obtained by fitting LSV data to the Tafel equation (η=a+b log |j|), where η is the overpotential, b is the Tafel slope, and j is the current density.
[0060] (3) Electrochemical impedance spectroscopy (EIS) is performed in the frequency range of 0.1 Hz to 100 kHz with an amplitude of 5 mV; chronopotentiometric method (CP) is used for long-term stability testing.
[0061] (4) Electrochemical double layer capacitance (Cdl) is used to measure the electrochemical active surface area (ECSA) and is determined by cyclic voltammetry (CV). CV tests are performed within a non-Radida potential window (1.03~1.13 V vs. RHE) at scan rates of 10, 20, 40, 60, 80 and 100 mV·s⁻¹.
[0062] (5) The long-term stability of the electrocatalyst under alkaline conditions was evaluated by constant current charge-discharge (CP) testing. The three-electrode system used the Fe-NPO electrocatalyst prepared in Example 1 as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode as the reference electrode. The electrolyte was a 1 mol·L⁻¹ KOH solution. Stability testing was conducted at a constant current density of 50 mA·cm⁻² for 24 h, and the potential change curve over time was recorded. The test results were used to evaluate the electrochemical durability of the electrocatalyst.
[0063] (6) The total hydrolysis performance of the catalyst was evaluated using a two-electrode system: an electrolysis system was constructed using Fe-NPO prepared in Example 1 as the anode (OER reaction) and Pt / C as the cathode (HER reaction) (denoted as PtC||Fe-NPO); and a system using Pt / C as the cathode and commercial RuO2 as the anode was used as a control (denoted as PtC||RuO2). The Pt / C cathode was prepared as follows: 20 wt% of commercial Pt / C catalyst was selected, dispersed in an ethanol / Nafion mixed solution (volume ratio 9:1), sonicated for 60 min, and then uniformly sprayed onto a nickel substrate, with the Pt loading controlled at 0.6 mg·cm⁻², and vacuum dried at 60 ℃ for later use. Performance testing was conducted using a constant voltage mode (1~2.5 V). Stability evaluation was performed using a DH7003 electrochemical workstation, with voltage decay behavior recorded for 100 h at a current density of 1000 mA·cm⁻². Simultaneously, polarization curves were acquired (scan rate 5 mV·s⁻¹) to complete the systematic characterization of the electrocatalyst performance.
[0064] The results of the above tests are as follows Figures 7 to 12 As shown.
[0065] (1) Figure 7 The LSV curve shows that the overpotential of the electrocatalytic material prepared in Example 1 is 219.6 mV under a current density of 10 mA·cm−2, indicating that the catalyst prepared in Example 1 has excellent catalytic activity.
[0066] (2) Figure 8The Tafel slope diagram shows that the electrocatalyst prepared in Example 1 has a Tafel slope of 44.50 mV·dec−1 in the OER process, indicating that the electrocatalyst prepared in Example 1 has a low Tafel slope value and exhibits faster reaction kinetics in the water electrolysis system.
[0067] (3) Figure 9 The electrocatalyst prepared in Example 1 has a smaller impedance as shown in the electrochemical impedance spectroscopy (EIS) diagram. This indicates that the electrocatalyst prepared in Example 1 has a smaller charge transfer impedance in the water electrolysis system, thereby achieving a faster electron transfer rate.
[0068] (4) Figure 10 Cyclic voltammetry (CV) plot ( Figure 10 (a) Recording different scan rates (10, 20, 40, 60, 80 and 100) within the non-Radida potential range The CV curve of ) Figure 10 (b) represents the current density (j) on the CV curve. c The slope of the straight line drawn between (ν) and the scan rate (ν) is C. dl The C value shows that the electrocatalyst Fe-NPO prepared in Example 1 has a high C value. dl The value is 2.06 The NPO for Comparative Example 1 was 1.26. The FPO of Comparative Example 2 was 1.28. This indicates that the Fe-NPO catalyst prepared in Example 1 has a large active specific surface area, which can not only promote charge transfer but also provide more active sites.
[0069] (5) Figure 11 The stability test (CP) graph shows that the electrocatalyst prepared in Example 1 remained stable after constant electrolysis at 50 mA·cm−2 for at least 24 hours in 1 mol·L−1 KOH electrolyte, indicating that it has good long-term stability.
[0070] (6) Figure 12 The image shows the two-electrode performance of the anion exchange membrane MEA water electrolysis device (HER-OER) assembled with the electrocatalyst from Example 1. The PtC‖Fe-NPO MEA device achieves a current density of 1 A·cm⁻² at a cell voltage of 1.76 V, while the control sample PtC‖RuO₂ MEA device requires 1.86 V to achieve the same current density. These results indicate that the Fe-NPO electrocatalyst prepared in Example 1 exhibits superior water electrolysis activity in the MEA device, requiring a lower voltage than the commercial RuO₂ catalyst to achieve the same current density, demonstrating its application potential in anion exchange membrane water electrolysis systems.
[0071] Example 2 The procedure is carried out in accordance with Example 1, except that the number of cycles is 2.
[0072] Example 3 The procedure is the same as in Example 1, except that the number of cycles is 10.
[0073] Example 4 The procedure was carried out in accordance with Example 1, except that Fe(NO3)3・9H2O was 0.041 g (0.005 mol / L).
[0074] Example 5 The procedure was carried out in accordance with Example 1, except that Fe(NO3)3・9H2O was 0.123 g (0.015 mol / L).
[0075] Example 6 The procedure was carried out in accordance with Example 1, except that copper foam was used as the working electrode.
[0076] Example 7 The procedure was carried out in accordance with Example 1, except that copper oxide was used as the working electrode.
[0077] Comparative Example 3 The procedure is the same as in Example 1, except that the potential window is -0.5V to 0.25V (vs. RHE).
[0078] Comparative Example 4 The procedure is the same as in Example 1, except that the potential window is -1.2V to 1.5V (vs. RHE).
[0079] Electrochemical performance tests were performed in the same manner as in Example 1, and the results are shown in Table 1.
[0080] Table 1 The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. An iron-doped nickel phosphate electrocatalytic material with asymmetric coordination-induced oxygen-rich vacancies, characterized in that, The material comprises a nickel phosphate substrate and Fe element doped in the nickel phosphate substrate, wherein the Fe element is in the form of Fe2+. 2+ and Fe 3+ It exists and forms an asymmetric Fe-O-Ni heterometallic oxygen bridge bond with Ni in the material through oxygen, and optionally forms an asymmetric Fe-OP-Ni heterometallic oxygen bridge bond with Ni in the material through oxygen and phosphorus, and the material also has oxygen vacancies.
2. The material according to claim 1, wherein, Based on the total amount of the material, the amount of Fe in the material is 2-3 at.%; And / or, based on the total amount of oxygen in the material, the amount of oxygen vacancies in the material is 50-60 at.%.
3. The material according to claim 1 or 2, wherein, The material is in the form of nanosheets, and multiple nanosheets of the material self-assemble to form nanoflowers.
4. The material according to claim 3, wherein, The thickness of the nanosheet-like material is 0.9-1.2 nm; And / or, the diameter of the self-assembled nanoflowers is 120-170 nm.
5. A method for preparing an iron-doped nickel phosphate electrocatalytic material with asymmetric coordination-induced oxygen-rich vacancies, characterized in that, The preparation method includes: Using a mixture containing nickel, iron, and phosphate sources as the electrolyte, electrodeposition was performed in a three-electrode system using cyclic voltammetry with a potential window of -0.95V to 1.2V (vs. RHE), thereby depositing iron-doped nickel phosphate electrocatalytic materials on the working electrode.
6. The preparation method according to claim 5, wherein, The number of electrodeposition cycles is 1-10, preferably 4-6.
7. The preparation method according to claim 5 or 6, wherein, The molar ratio of nickel in the nickel source, iron in the iron source, and phosphate in the phosphate source in the electrolyte is 3:0.5-1.5:
1. Preferably, the concentration of nickel in the nickel source of the electrolyte is 0.03 mol / L, the concentration of iron in the iron source is 0.005-0.015 mol / L, and the concentration of phosphate in the phosphate source is 0.01 mol / L.
8. The preparation method according to claim 5 or 6, wherein, The nickel source is selected from at least one of nickel sulfate, nickel chloride, nickel nitrate, nickel acetate, and nickel aminosulfonate and their corresponding hydrates; And / or, the iron source is selected from at least one of ferric nitrate, ferrous sulfate, ferrous ammonium sulfate, and ferrous chloride and their corresponding hydrates; And / or, the phosphate source is selected from sodium hypophosphite and / or potassium hypophosphite.
9. The preparation method according to claim 5, wherein, In the three-electrode system, the working electrode is a nickel electrode, the counter electrode is a Pt electrode, and the reference electrode is selected from at least one of a saturated calomel electrode, an Ag / AgCl electrode, and a mercuric oxide electrode.
10. The application of an iron-doped nickel phosphate electrocatalyst material according to any one of claims 1-4 or an iron-doped nickel phosphate electrocatalyst material prepared by any one of claims 5-9 in hydrogen production by water electrolysis.